Joining the fray outside military intervention in civil wars - Shirkey, Zachary C. (Military strategy and operational art, 2012)
Building on his earlier volume, Is this a Private Fight or Can Anybody Join?, Zachary C. Shirkey looks at how the decision to join a civil war can be intuitively understood as follows.